PENINGKATAN KUALITAS PRODUKSI RENGGINANG KETAN MENGGUNAKAN TEKNOLOGI PENGERING BUATAN - Saptariana, Saptariana; Putri, Meddiati Fajri; Agustina, Titin (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2014)
Rengginang is one of Indonesian traditional food made from glutinous rice ingredient white or black, generally in the form of a circle of a certain size, taste sweet or savory, and have a crisp texture. Based on surveys and interviews directly to employer partners, pernasalahan which can be grouped into three aspects: 1). The production aspect, for this small entrepreneurs are still using technology rengginang glutinous drying naturally., 2). The quality aspect, drying techniques used in rengginang causing substances do not meet the standard of food in accordance with SNI. In addition, the packaging has not been done properly and the result produced rengginang perishable or quickly fizzled, 3). Aspects of Business Management and Marketing. During this segment of the market rengginang production glutinous mother and mother Kartini Murti Mardiyah about 90% for the traditional market Pecangaan districts, the district of Jepara.